1997
DOI: 10.1007/s004120050236
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescent in situ hybridization (FISH) analysis of the relationship between chromosome location and nuclear morphology in human neutrophils

Abstract: Human neutrophil nuclei typically consist of three of four large heterochromatic lobes joined by thin, DNA-containing filaments. In addition, some lobes exhibit appendages of various sizes and shapes. Classical genetic and cytological studies suggest that some appendages contain specific chromosomes. The studies reported here provide the first detailed analysis of the spatial relationship between individual chromosomes and recognizable structures in neutrophil nuclei using fluorescent in situ hybridization. An… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
2

Year Published

1999
1999
2015
2015

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(56 citation statements)
references
References 50 publications
3
51
2
Order By: Relevance
“…Likewise, in males, the Y chromosome may be found in a club-shaped minor lobe (96). These observations led Sanchez et al (138) to question whether the major lobes of the neutrophil nuclei also had characteristic chromosome contents. They investigated the distribution of the sex chromosomes and autosomes 2 and 18 by using chromosome paints and found the distribution of chromosomes in the major lobes to be variable, although there were significant biases toward cosegregation of the two X chromosomes in four lobed female neutrophils and of both homologues in the same lobe.…”
Section: Nuclear Differentiation Without Polyploidymentioning
confidence: 99%
“…Likewise, in males, the Y chromosome may be found in a club-shaped minor lobe (96). These observations led Sanchez et al (138) to question whether the major lobes of the neutrophil nuclei also had characteristic chromosome contents. They investigated the distribution of the sex chromosomes and autosomes 2 and 18 by using chromosome paints and found the distribution of chromosomes in the major lobes to be variable, although there were significant biases toward cosegregation of the two X chromosomes in four lobed female neutrophils and of both homologues in the same lobe.…”
Section: Nuclear Differentiation Without Polyploidymentioning
confidence: 99%
“…A number of experiments revealing the regularities of higher-order chromatin structure have been done using spherical cell nuclei such as lymphocytes or the oval nuclei of fibroblasts (T. Cremer et al 1993;Ferreira et al 1997;Croft et al 1999;Sadoni et al 1999;Skalníková et al 2000); however, restricted information is available concerning higher-order chromatin structure in segmented granulocytes (Sanchez et al 1997;Grigoryev and Woodcock 1998;Sanchez and Wangh 1999;Alcobia et al 2000). It was found that cell nuclei are compartmentalised in spherical cells; chromatin in interphase cell nuclei is arranged in spatially separated chromosome territories (Manuelidis 1985;Lichter et al 1988;Leitch et al 1990;C.…”
Section: Introductionmentioning
confidence: 96%
“…Our experiments on the higher-order chromatin structure of human granulocytes, mainly the neutrophils, represent a continuation of the observations of Sanchez et al (1997) and Sanchez and Wangh (1999). These authors focused their studies on the nuclear location of chromosomes X and Y and the degree of condensation of chromosomes 2 and 18.…”
Section: Introductionmentioning
confidence: 97%
“…The results published so far on somatic pairing of human homologs are discordant. In neutrophil nuclei, there appears to be a tendency of homolog chromosomes to partition into the same lobe during differentiation, although pairing of homologs is not observed (Aquiles Sanchez et al, 1997). Human lymphocytes exhibit a late S phase-restricted association of chromosomes 15 at the imprinted 15q11 → q13 region (LaSalle and Lalande, 1996).…”
Section: Intranuclear Positioning Of Chromosomesmentioning
confidence: 99%